2018
DOI: 10.1002/star.201700192
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated and Cross‐Linked Wheat Starches in the Presence of Polyethylene Oxide and Their Application in Biocomposite Films

Abstract: Wheat starch is modified by phosphorylation and cross‐linking. Starches are evaluated for phosphorus content, amylose content, swelling power, solubility, pasting properties, crystallinity, and morphology. Films are made with phosphorylated and cross‐linked starches, and with addition of 10% (w/w) polyethylene oxide (PEO). The films are evaluated for morphology, water vapor permeability, mechanical properties, crystallinity, roughness, and angle of contact with water. Phosphorylated starch shows higher phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Moreover, by reacting with the OH-groups of starch, cross-linking agents make starch less hydrophilic, which might account for the increased network resistance of the films. Some earlier studies also confirmed our results of increased tensile strength of CL starch films [33,54].…”
Section: Mechanical Propertiessupporting
confidence: 91%
“…Moreover, by reacting with the OH-groups of starch, cross-linking agents make starch less hydrophilic, which might account for the increased network resistance of the films. Some earlier studies also confirmed our results of increased tensile strength of CL starch films [33,54].…”
Section: Mechanical Propertiessupporting
confidence: 91%
“…The results showed that cross-linked starch films have higher TS than native starch films. Bruni et al [ 58 ] also reported a similar increase in TS in cross-linked corn starch films compared to native film. They concluded that adding a cross-linking agent provides stronger intermolecular interactions in the starch network.…”
Section: Resultsmentioning
confidence: 73%
“…The amount of amylose in various starch was measured using colorimetric assays described by Zavareze group (Bruni, Oliveira, Halal, & Flores, 2017). Briefly, 100 mg of the samples was added to 100-ml flasks and mixed with 96° GL ethanol and 1 mol/L NaOH.…”
Section: Amylose Contentmentioning
confidence: 99%